A rare case of Sprengel deformity associated with spondylocostal dysostosis in a four-year child - Mohamed, Syed; Kumar, Radha (International Journal of Contemporary Pediatrics, 2019)
Sprengel deformity is a complex congenital anomaly affecting one or both scapulae with mispositioning and dysplasia of scapula. It occurs due to failure of descent of scapula during intrauterine development and is the commonest congenital skeletal deformity of the scapula, often associated with other skeletal deformities. spondylocostal dysostosis is a rare genetic disorder which is characterized by malformation of the bones of the spine and ribs. It occurs in approximately 1 in 2,00,000 people worldwide. In spondylocostal dysostosis, affected children have wedge shaped vertebrae along with ribs that are fused, forked or sometimes missing. Based on the severity of the defect’s children may present with short stature, scoliosis or hypoplasia of lungs causing difficulty in breathing and recurrent respiratory tract infections. Management of both these skeletal deformities depends on their severity and the presence of associated deformities. Surgical intervention might be required for cosmetic and functional recovery of the shoulder. Authors had a rare and interesting case of a 4-year-old boy who had features of Sprengel deformity affecting left scapula which was associated with features of spondylocostal dysostosis.